Dealing With the Aftermath of Mass Disasters: A Field Study on the Application of EMDR Integrative Group Treatment Protocol With Child Survivors of the 2016 Italy Earthquakes - Trentini, Cristina; Lauriola, Marco; Giuliani, Alessandro; Maslovaric, Giada; Tambelli, Renata; Fernandez, Isabel; Pagani, Marco (Frontiers in Psychology, 2018)
This study explored the effects of the EMDR Integrative Group Treatment Protocol (EMDR-IGTP) on child survivors of the earthquakes that struck Umbria, a region of central Italy, on August 24th and on October 26th 2016. Three hundred and thirty-two children from the town of Norcia and nearby severely disrupted villages received 3 cycles of EMDR-IGTP. The Emotion Thermometers (ET-5) and the Children's Revised Impact of Event Scale (CRIES-13) were administered before (T0) and about 1 week after the conclusion of the third cycle (T3) of EMDR-IGTP. At T3, older children showed a reduction of distress and anger, whereas younger children reported an increase on these domains; moreover, older children reported a greater reduction of anxiety than younger ones. A greater reduction of distress, anxiety, and need for help was evidenced in females, whereas a greater improvement in depressive symptoms was evidenced in males. The effects of the EMDR-IGTP treatment on post-traumatic symptoms were particularly evident in older children, compared to younger ones, and marginally greater in females than in males; moreover, a greater improvement was found in children who had received a timelier intervention, than in those who received delayed treatment. These results provide further evidence for the utility of EMDR-IGTP in dealing with the extensive need for mental health services in mass disaster contexts. Also, these data highlight the importance of providing EMDR-IGTP in the immediate aftermath of a natural disaster, to contribute significantly in restoring adaptive psychological functioning in children, especially in older ones.